Keterampilan Decoupage Untuk Peningkatan Perekonomian Ibu Rumah Tangga Di Kelurahan Sendang Sari Kisaran - Hommy Dorthy Ellyany Sinaga; Novica Irawati (Universitas Muhammadiyah Sumatera Utara, 2018)
The community service activity targeted at 14 housewives from Sendang Sari Village, Kisaran Barat, Asahan is aimed to provide decoupage craft skills training which will be expected with skills and this knowledge will be able to help improve the economic well-being of the household. The implementation method is carried out by providing training in the form of a workshop to use decoupage technique on the wallet. All participants (100%) responded positively to thi training activities provided.